Análise de Polimorfismos de Nucleotídeos Únicos (SNPs) em pacientes com câncer de cabeça e pescoço - Ruiz, Mariangela Torreglosa (2008)
Head and neck cancer is responsible for a high death rate. Single nucleotide polymorphisms (SNPs) are the most common variation of human genome and can be associated to the molecular basis of cancer. Objectives: To establish the incidence of this disease in the Otorhinolaryngology and Head and Neck Surgery Service of Hospital de Base in São José do Rio Preto; to investigate the frequency of SNPs in the MTR, VEGF, KiSS-1, NINJ1, TAX1BP1 and LAD1 genes in head and neck cancer patients and a control population; to evaluate the association of these polymorphisms with smoking, alcoholism, gender and age and to verify the association between polymorphisms and clinicopathological features of the disease. Subjects and Methods: The epidemiological data of head and neck cancer patients consulted in the Otorhinolaryngology and Head and Neck Surgery Service in the period from 2000 to 2005 were analyzed. Eight hundred and five individuals (254 head and neck cancer patients and 551 controls) were included in the study for molecular investigation. The molecular analyses were performed with genomic DNA utilizing Real Time PCR (VEGF gene), PCR-SSCP (KiSS-1 gene), PCR RFLP (MTR, NINJ1 and TAX1BP1 genes) and automatic sequencing (LAD 1 gene) techniques. Results: An analysis of epidemiological data shows a prevalence of men (86%), smokers (83%) and alcoholics (77.95%). The most common primary tumor site was the oral cavity (35.37%). Statistical differences were found in the MTR A2756G polymorphism distribution (OR = 1.69; CI 95% 1.09-2.62; p = 0.019) by molecular analysis between patients and controls. On analyzing the primary tumor site, an increased frequency of KISS-1 polymorphic alleles was identified in laryngeal cancer (OR = 2.32; 95% CI 1.12 4.82; p = 0.02); an increased frequency of the NINJ1 polymorphism was found in oral cavity cancer (OR = 1.86; 95% CI 1.05-3.30; p = 0.03) and a decreased frequency in laryngeal cancer (OR = 0.40; 95% CI 0.22-0.74; p = 0.003); and an increase of the TAX1BP1 gene polymorphism was seen in oral cavity cancer (OR = 2.25; 95% CI 1.20-4.21; p = 0.01). A decreased frequency of the VEGF gene polymorphism was observed in advanced (T3 and T4) tumors (OR = 0.36; CI 95% 0.14-0.93; p = 0.0345) and a lower frequency of the LAD1 polymorphism in stage III and IV tumors (OR = 0.39 95% CI 0.18-0.83; p = 0.01). Conclusions: Head and neck cancer is more frequent in men, smokers and alcoholics with the most common primary tumor site being the oral cavity. MTR A2756G is associated with head and neck cancer. There is evidence of an association between this polymorphism and smoking, alcoholism, gender and age. There is also evidence of an association between the KiSS-1 gene polymorphism and laryngeal cancer, of NINJ1 and TAX1BP1 polymorphisms in oral cavity tumors, lower frequencies of the VEGF polymorphism in T3 and T4 tumors and the LAD1 polymorphism in stage III and IV tumors.